Evolution of Sedimentary Facies of the Ordovician-Silurian Transition and Its Response to the Guangxi Movement in Southern Sichuan Basin, China - Guoyou Fu; Zhensheng Shi; Meng Zhao; Qun Zhao; Tianqi Zhou; Ling Qi; Pengfei Wang (Applied Sciences)
The formation and distribution of sedimentary facies of the Wufeng Formation reflect the evolution of Guangxi Movement and significantly impact shale reservoir quality in southern Sichuan Basin, China. This study characterizes the sedimentary facies and their evolution of Ordovician-Silurian transition shale based on detailed core descriptions, full-scale imaging of large slabs, and field emission scanning electron microscopy of argon-ion polished sections. There only exist fine-grained turbidite deposits, hemipelagic deposits, and shallow shoal deposits for the Wufeng shale. Fine-grained turbidite deposits consist primarily of clastic quartz and clay minerals and can be divided into nine subdivisions. Hemipelagic deposits are mainly composed of quartz, detrital carbonate, and clay minerals. Shallow shoal deposits are dominated by clay minerals, dolomite, and calcite, with carbonates primarily of autochthonous origin. The fine-grained turbidite deposits predominantly occur within the Dicellograptus complanatus and D. complexus graptolite biozones, while hemipelagic deposits are confined to the Paraorthograptus pacificus biozone, and shallow shoal deposits are restricted to the Metabolograptus extraordinarius biozone. Formation and distribution of the three sedimentary facies are closely related to the Guangxi Movement. During the strong tectonic compression stage, sufficient sediment supply and intensive volcanic eruption favored the formation of the fine-grained turbidite deposits. Along with waning tectonic activity and reduced terrestrial input, hemipelagic deposits formed and then shallow shoal deposits. Sedimentary facies exert first-order controls on shale reservoir quality, with hemipelagic deposits exhibiting optimal reservoir characteristics. Laboratory analyses reveal that hemipelagic facies possess the highest porosity (3.34–4.15%) and TOC content (2.91–4.10%) due to biogenic quartz enrichment and minimal allochthonous dilution, whereas fine-grained turbidites show degraded properties (porosity: 1.58–3.81%; TOC: 0.15–2.6%) from high-energy siliciclastic influx. Shallow shoal deposits display intermediate values (porosity: 3.92%; TOC: 3.25%), constrained by carbonate cementation.